Blood Rheology, Cardiovascular Risk Factors, and Cardiovascular Disease: The West of Scotland Coronary Prevention Study - Lowe, Gordon; Rumley, Ann; Norrie, John; Ford, Ian; Shepherd, James; Cobbe, Stuart; Macfarlane, Peter; Packard, Christopher; The West of Scotland Coronary Prevention Study Group; on behalf of (Thrombosis and Haemostasis, 2000)
The West of Scotland Coronary Prevention Study (WOSCOPS) showed that pravastatin reduced the risk of coronary heart disease (CHD) events in 6,595 middle-aged hypercholesterolaemic men aged 45–64 years without prior myocardial infarction followed for an average of 4.9 years. We hypothesised prospectively (a) that baseline levels of haemorheological variables were related to baseline and incident CHD and to mortality; and (b) that reduction in lipoproteins by pravastatin would lower plasma and blood viscosity, a potential contributory mechanism to CHD events. We therefore studied plasma and blood viscosity, fibrinogen, haematocrit, and blood cell counts at baseline and 1 year. At baseline, plasma and blood viscosity were related to risk factors, CHD measures, and claudication. On univariate analysis, baseline levels of all rheological variables (except platelet count) were related to incident CHD; CHD mortality; and total mortality. On multivariate analysis including baseline CHD and risk factors, plasma and blood viscosity, haematocrit and white cell count each remained significantly associated with incident CHD; while fibrinogen remained an independent predictor of mortality (all p < 0.03). After one year, lipoprotein reduction by pravastatin was associated with significant reductions (about one quarter of a standard deviation) in plasma viscosity (mean difference 0.02 mPa.s, p <0.001) and in blood viscosity (mean difference 0.06 mPa.s, p <0.001), but was not associated with significant changes in other rheological variables. We therefore suggest that pravastatin therapy, which reduces elevated lipoproteins in hypercholesterolaemic men, may lower risks of CHD and mortality partly by lowering plasma and blood viscosity. Further studies are required to test this hypothesis.
Keywords: Rheology; viscosity; coronary heart disease; lipoproteins; pravastatin